Exploring Relationship of Bhujel With the Kirati Languages - Regmi, Dan Raj (Gipan, 2025)
This paper explores the relationship of the Bhujel language with the Kirati languages spoken in distinct geographical regions of Nepal in terms of participant reference marking from a typological perspective. Bhujel which is mainly spoken in Tanahun, Gorkha, Chitwan and Nawalpur has been genetically assumed to be closely related to Chepang, a central Himalayish language. However, unlike in Kirati, there are disagreements among the linguists in relation to the genetic membership of the Bhujel language. The Kirati languages, which are spoken in the eastern part of Nepal, are genetically affiliated with Eastern Himalayish sub-group. The Kirati languages which have been typologically described as having complex verb morphology registering person, number and clusivity in the complex of the verb in terms of the hierarchy of the participants in the clause. This paper argues that Bhujel, to a great extent, shares many of the features of participant reference with the Kirati languages. Due to contact, Bhujel also shares some participant reference features with Chepang. However, typologically, Bhujel does not significantly seem to be related with Chepang in which both agent and patient are marked at a time in a clause. In due course of time, the third person marker used in the Kirati languages has been innovated in Bhujel as direct marker. As typologically Bhujel and Kirati languages are related, the genetic membership of Bhujel necessitates being re-established/revised with the Kirati languages.